Effects of Yeast Extract Addition in Diet on Performances and Feather Pecking of Pullets When Raising under Feed Restriction and Litter Removal - Mathlouthi , N.; Ballet, N.; Larbier, M. (International Journal of Poultry Science, 2011)
This study was performed with pullets to evaluate the effects of dietary yeast extract on bird performances and feather pecking. A total of 2400, 10-weeks-old pullets were divided into 8 groups: C, R, L and LR are control, feed restriction (from 09h00 to 15h00), litter removal (from 12 to 17 weeks of age) and both feed restriction and litter removal groups, respectively. CA, RA, LA and LRA groups received the diet supplemented with yeast extracts. The dietary yeast extract additive was used at the dose of 50 mg per kg live weight. The experiment lasted 8 weeks. Body weight, feed intake and feather pecking were recorded. Litter removal and/or feed restriction affected the growth rate of pullets and increased the frequency of feather pecking. The yeast extract dietary addition did not have any influence when animals were fed ad libitum, but significantly alleviated the feed restriction and litter removal effects. The results of the pecking observations showed that RA, LA and LRA groups had less frequency of gentle pecks and severe pecks compared to R, L and LR groups. In addition, pullets fed C and CA diets had the lowest frequency of gentle pecks (12.65 and 19.45%, respectively) and severe pecks (0.23 and 0.17%, respectively) compared to R, L and LR groups. In conclusion, the dietary addition of yeast extract could reduce significantly the feather pecking as well as the depressive effects of feed restriction and/or litter removal on body weight gain.